Supplementary Table S11 from SPOP Mutations Target STING1 Signaling in Prostate Cancer and Create Therapeutic Vulnerabilities to PARP Inhibitor–Induced Growth Suppression - Chuandong Geng (17315310) (2025)
Supplemental Table S11. Quantification of each protein-specific band normalized to vinculin (C4-2b–derived models, Fig. 4E).